A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil - Neto, Jaime De Liege Gama; Passos, Mahedy Araujo Bastos (Zootaxa, 2017)
A new species of Campylocia is described from Northern Brazil based on male and female imagoes. The main characteristics that distinguish the male imago of the new species from its congeners are: forewings with fork of Rs basal to fork of MA and one or two intercalary veins attached to CuA; general color of abdomen whitish; terga I–VIII with purplish brown dorsolateral area and light colored medial line; terga II–VII with two pairs of light colored drop-shaped spots (one medioapical and one medial); tergum VIII with a medioapical pair of light colored drop-shaped spots; terga IX–X orange; base of penis rectangular; penis lobes adjacent to medial line, laterally directed, without median lobes, fused on basal 1/2 and slender on distal 2/3; subgenital plate rectangular with medial emargination and dark brown margins.